2010
DOI: 10.1159/000299475
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 36 Different Weight Estimation Formulae in Fetuses with Macrosomia

Abstract: Introduction: The aim of this retrospective clinical study was to compare the accuracy of 36 commonly used weight estimation formulae in macrosomic fetuses. Material and Methods: Ultrasound estimation of fetal weight (FW) was carried out within 7 days up to delivery in 350 singleton fetuses with a birth weight (BW) of ≧4,000 g. The accuracy of the different formulae for FW estimation was compared by, firstly, the mean percentage (MPE) and mean absolute percentage error (MAPE), secondly, by the frequency distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 109 publications
3
73
2
4
Order By: Relevance
“…A new Hart formula, which included fetal biometry and maternal weight, was retrospectively compared with seven widely accepted weight formulae in 424 singleton fetuses >4,000 g; 77.9% of estimates fell within ±5% of the actual weight at birth, 97.1% within ±10%, and 100% within ±15-20%, and compared with other formulae, the new formula exhibited the smallest mean error, the smallest mean percentage error, and the lowest mean absolute percentage error [26]. A more recent study demonstrated that the Hart formula was the most accurate of 36 formulae, and the frequency distribution of the differences between estimated fetal weight and birth weight was only slightly lower than the original data; however, the new Hart formula detected all fetuses >4,000 g but none of the 29 fetuses >4,500 g. The highest detection rate for fetuses >4,500 g was achieved with the Hadlock IV formula (HC, AC, FL) (74.5%), but at a false positive rate of 31.5% [27]. To overcome the problem that weight formulas designed for macrosomic fetuses bear the risk to be accidently used in with a birth weight <4,000 g, Kehl et al [28] developed a formula for optimal fetal weight estimation with an AC ≥36 cm.…”
Section: Diagnosis Of Fetal Macrosomia By Ultrasoundmentioning
confidence: 90%
“…A new Hart formula, which included fetal biometry and maternal weight, was retrospectively compared with seven widely accepted weight formulae in 424 singleton fetuses >4,000 g; 77.9% of estimates fell within ±5% of the actual weight at birth, 97.1% within ±10%, and 100% within ±15-20%, and compared with other formulae, the new formula exhibited the smallest mean error, the smallest mean percentage error, and the lowest mean absolute percentage error [26]. A more recent study demonstrated that the Hart formula was the most accurate of 36 formulae, and the frequency distribution of the differences between estimated fetal weight and birth weight was only slightly lower than the original data; however, the new Hart formula detected all fetuses >4,000 g but none of the 29 fetuses >4,500 g. The highest detection rate for fetuses >4,500 g was achieved with the Hadlock IV formula (HC, AC, FL) (74.5%), but at a false positive rate of 31.5% [27]. To overcome the problem that weight formulas designed for macrosomic fetuses bear the risk to be accidently used in with a birth weight <4,000 g, Kehl et al [28] developed a formula for optimal fetal weight estimation with an AC ≥36 cm.…”
Section: Diagnosis Of Fetal Macrosomia By Ultrasoundmentioning
confidence: 90%
“…Recently, Hoopmann et al [19] compared the performance of 36 different weight estimation formulae in fetuses with macrosomia. They noted that among all formulae the mean detection rates for fetuses with a BW ≥4,000, ≥4,300 and ≥4,500 g were low (29, 24 and 22%, respectively) for impressively high false positive rates (12 and 7%).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and reliability of these formulas may differ and low values can adversely affect physicians' decisions. The performance of formulas may also be different in macrosomic fetuses (>4,000 g) or low-birth-weight fetuses (<2,500 g) [15,16,17,18,19,20]. Therefore, it is very important to use the most reliable and accurate formula when predicting the fetal weight.…”
Section: Introductionmentioning
confidence: 99%
“…The mean percentage error (MPE) as well as the mean absolute percentage error (MAPE) of the formulae depend on the weight itself. It is thus not surprising both for underweight infants or, respectively, pre-term infants as well as for infants with macrosomia, that the weight estimations can exhibit a clinically relevant error susceptibility [6][7][8]. However, it is just this delineation of the normal weight collective from the abnormally under-or overweight fetuses that is of decisive importance for the prenatal and obstetric management.…”
mentioning
confidence: 99%